Prevalence of Carbapenem resistant Klebsiella pneumoniae in North India (Global Journal of Medical Research, 2021)
Abstract not found
Keywords: carbapenem-resistant klebsiella pneumoniae (CRKP); carbapenem-sensitive klebsiella pneumoniae (CSKP)